Model Korelasi Antara Lama Perendaman Campuran Perkerasan AC-WC terhadap Karakteristik Marshall - Alik Ansyori Alamsyah; Azhar Adi Darmawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Roads are a means of land transportation composed of several materials, such as bitumen, filler, coarse aggregate, and fine aggregate. Water is a common cause of damage during maintenance. This study aims to determine how immersion (water) affects Marshall properties such as stability, plastic fatigue, Marshall yield, and air voids. For statistical testing, three x nine cylindrical test specimens weighing 1200 grams were manufactured with an optimum asphalt content of 7.30%. In this study, three specimens were used, each with immersion times of 2, 4, 6, 8, 10, 12, 24, 48, and 72 hours. The results showed that soaking affected Marshall Stability, Plastic Yield, Marshall Yield, and Air Voids in the properties of the AC-WC mixture. Marshall Stability, the equation is: Y = -10.67x + 2288.5. Marshall Stability is expected to reach the requirements after 172.31 hours. The equation for the plastic yield strength is Y = 7E-05x2 – 0.0291x + 3.4923. The Marshall Yield Value can be found using the following equation: Y = -0.0042X2 + 0.3556X + 6.1448. After 95.5 hours, the Marshall Quotient is estimated to be below the required value. The equation for the air void value is Y = 0.0006X2 - 0.072X + 5.1632. The air void value is estimated to be below the required value after 20 hours.